The Non-invasive studies can replace to preoperative arteriography - Rudnitzky, Omar; Davezac, Víctor (Cirugía del Uruguay, 1995)
A revascularization tria/ was carried out in 150 patients with severe ischemia of the lower limbs. Preoperative arteriography was avoided. Al! patients were evaluated by means of eco-Ooppler and Ooppler. lt was pro ved that non-invasive studies had a GPV of 97% far predicting the possibility of revascularization; that they made possible the corree/ definition of the afferent vessel of the bypass in al! cases and that they defined the efferent vessel of the bypass with a GPV of 92%. By adding intraoperative pre-procedure arteriography, this value rose to more than 99%. lt is concluded that non-invasive studies make possible the avoidance of preoperative arteriography in patients with severe ischemia of the lower limbs.